Adaptive Control of M3c-Based Variable Speed Drive for Multiple Permanent-Magnet-Synchronous-Motor-Driven Centrifugal Pumps - Travieso-Torres, J; Diaz-Diaz, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
There has been growing interest in using permanent magnet synchronous motors (PMSMs) for pumping applications to improve energy efficiency. One promising approach for powering these motors in variable speed applications is using an M3C due to its inherent fault tolerance capability. However, M3C converters require a more complex control system than simpler converters. For instance, a basic M3C control system for power transmission requires seventeen PI controllers, whose fixed adjustment depends on the M3C’s dynamical model parameters’ value knowledge, needing initial extensive and time-consuming testing to obtain it. As an alternative, we propose an adaptive M3C control system for variable speed drives powering multiple PMSM-driven centrifugal pumps that reduces the number of controllers to six. Furthermore, the proposal does not require initial knowledge of the converter, motor, or load parameters, making it more practical and versatile. The proposal introduces an ad hoc hybrid passivity-based model reference adaptive controller in cascade with a passivity-based control. It was validated through theoretical stability proof and comparative simulation results with a basic control system under normal and fault operations. As a result, the proposal effectively follows the required rotor speed while enhancing performance by decreasing the current consumption and recovering from a (Formula presented.) input phase imbalance, a cell short circuit, an open cell, and parameters changes of the motor–pump set. © 2023 by the authors.